ANALISIS PEMASARAN BAWANG MERAH DIKECAMATAN SANDEN KABUPATEN BANTUL - Maya Severlina (Jurnal Dinamika Sosial Ekonomi, 2010)
Marketing analysis of Red Onion in Sanden Sub District Bantul Regency This research aims to know the of profit difference, the margin difference, and the efficiency difference of Red Onion Marketing channels in Bantul Regency. The method that is used in this research is survey method. To determine the research location is used purposive method to get the sample of the farmers and trailers is used snowball sampling method. There are twelve farmers, twelve retailers, eight merchant wholesalers, and four wholesalers taken in this research. This research also requeires the primary and secondary data. To analyze the difference to profit received by red onion trades channels I, channels II, and channels III used channel profit analysis. Then, to analyze the deference of margin in the tree marketing channels uses margin analysis. Meanwhile, to analyze deference of efficiency in the three marketing channels uses efficiency analysis. The result of this research shows that the differences of profit received by traders of the three marketing channels significant; then the difference of margin between the three marketing channels is significant; then the deference of margin between the three marketing channels significant; while the deference of efficiency between the three marketing channels significant.Keywords : Red Onion, Proft, Margin, Efficiency